Gorski turizem - Eiselt, Irena
The beginnings of mountain tourism in Slovenia reach back to the second half of the 19th century. This was a time of an awakening mountaineering consciousness that showed itself primarily in the build of mountain huts, walking paths, and climbing routes. All these efforts gradually led to the foundation of the Slovenian Mountaineering Association (1893) that in the following decades contributed greatly to the development of mountaineering and alpinist culture. The enhanced interest in mountain hiking that was and remains to be the driving force of mountain tourism also brought about a boom in mountain photography and an increasing popularity of mountain postcards.In this digital collection we present different material that is to highlight the history of mountain tourism in Slovenia. It is comprised of mountain photographs, a part of the mountain postcards preserved by the National and University Library, and a series of portraits of the fathers of Slovenian mountaineering.
The beginnings of mountain tourism in Slovenia reach back to the second half of the 19th century. This was a time of an awakening mountaineering consciousness that showed itself primarily in the build of mountain huts, walking paths, and climbing routes. All these efforts gradually led to the foundation of the Slovenian Mountaineering Association (1893) that in the following decades contributed greatly to the development of mountaineering and alpinist culture. The enhanced interest in mountain hiking that was and remains to be the driving force of mountain tourism also brought about a boom in mountain photography and an increasing popularity of mountain postcards.In this digital collection we present different material that is to highlight the history of mountain tourism in Slovenia. It is comprised of mountain photographs, a part of the mountain postcards preserved by the National and University Library, and a series of portraits of the fathers of Slovenian mountaineering.